SOCIAL SERVICE USE GOOGLE-GROUPS INTO THE CURRICULUM AND EDUCATIONAL ACTIVITIES - Nosenko, T.I. (Journal of Information Technologies in Education (ITE), 2010)
The article considers the use of Web2.0 services for organizing training activities high school teachers, formulated and analyzed the benefits of using social services issues in educational purposes. Determined that united in groups, students of pedagogical universities, thus preparing for the profession, enhancing professional knowledge.